Short- and longer-term health-care resource utilization and costs associated with acute ischemic stroke - Johnson BH; Bonafede MM; Watson C (Dove Medical Press, 2016)
Barbara H Johnson,1 Machaon M Bonafede,1 Crystal Watson2 1Outcomes Research, Truven Health Analytics, Cambridge, MA, USA; 2Health Economics and Outcomes Research, Biogen, Cambridge, MA, USA Objectives: The mean lifetime cost of ischemic stroke is approximately $140,048 in the United States, placing stroke among the top 10 most costly conditions among Medicare beneficiaries. The objective of this study was to describe the health-care resource utilization and costs in the year following hospitalization for acute ischemic stroke (AIS).Methods: This retrospective claims analysis quantifies utilization and costs following inpatient admission for AIS among the commercially insured and Medicare beneficiaries in the Truven Health databases. Patients who were 18 years or older and continuously enrolled for 12 months before and after an AIS event occurring (index) between January 2009 and December 2012 were identified. Patients with AIS in the year preindex were excluded. Demographic and clinical characteristics were evaluated at admission and in the preindex, respectively. Direct costs, readmissions, and inpatient length of stay (LOS) were described in the year postindex.Results: The eligible populations comprised 20,314 commercially insured patients and 31,037 Medicare beneficiaries. Average all-cause costs were $61,354 and $44,929 (commercial and Medicare, respectively) in the first year after the AIS. Approximately 50%–55% of total 12-month costs were incurred between day 31 and day 365 following the incident AIS. One quarter (24.6%) of commercially insured patients and 38.8% of Medicare beneficiaries were readmitted within 30 days with 16.6% and 71.7% (commercial and Medicare, respectively) of those having a principal diagnosis of AIS. The average AIS-related readmission length of stay was nearly three times that of the initial hospitalization for both commercially insured patients (3.8 vs 10.8 days) and Medicare beneficiaries (4.0 vs 10.8 days).Conclusion: In addition to the substantial costs of the initial hospitalization of an AIS, these costs double within the year following this event. Given the high cost associated with AIS, new interventions reducing either the acute or longer-term burden of AIS are needed. Keywords: acute ischemic stroke, health-care resource utilization, health-care costs, readmissions